2017
DOI: 10.1007/s10826-017-0830-5
|View full text |Cite
|
Sign up to set email alerts
|

Self-Report Measures of Parental Self-Efficacy: A Systematic Review of the Current Literature

Abstract: Parenting self-efficacy (PSE) describes a parent’s belief in their ability to perform the parenting role successfully. Higher levels of PSE have consistently been shown to be correlated with a wide range of parenting and child outcomes. Consequently, many parenting interventions aim to improve PSE. PSE measurement has typically been via self-report measures. However, the wide range of available measures has resulted in their limited use, inconsistent terminology and ambiguous theoretical grounding. The purpose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
145
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(161 citation statements)
references
References 77 publications
1
145
0
4
Order By: Relevance
“…Despite its different theoretical origins, most recent studies have considered the PSOC as a measure of parenting self-efficacy from the perspective of Bandura's theory (Vance & Brando 2017;Wittkowski, Garrett, Calam, & Weisberg, 2017). This theory (Bandura, 1997) contemplates several levels of perception of self-efficacy, and the PSOC has been considered as a general-domain self-efficacy parenting questionnaire (Vance & Brando, 2017).…”
mentioning
confidence: 99%
“…Despite its different theoretical origins, most recent studies have considered the PSOC as a measure of parenting self-efficacy from the perspective of Bandura's theory (Vance & Brando 2017;Wittkowski, Garrett, Calam, & Weisberg, 2017). This theory (Bandura, 1997) contemplates several levels of perception of self-efficacy, and the PSOC has been considered as a general-domain self-efficacy parenting questionnaire (Vance & Brando, 2017).…”
mentioning
confidence: 99%
“…A recent systematic review of PSE measures identified no measures of PSE that had been developed specifically for parents of adolescents (Wittkowski, Garrett, Calam, & Weisberg, 2017). However, this review excluded narrow-domain measures.…”
Section: The Need For a New Pse Measurementioning
confidence: 99%
“…Most researchers select items based on a review of the literature, followed by evaluation by a panel of experts (e.g., Abidin, 1990;Ballenski & Cook, 1982;Dumka et al, 1996). A systematic review of measures of PSE found that of the 34 measures included, only 41.18% of studies used a factor analytic approach as part of their validation, and 20.59% reported no information on internal consistency (Wittkowski et al, 2017). Validation of the above-mentioned scale created by Ballenski and Cook (1982) was limited to establishing two-week test-retest reliability with a subsample of 23 mothers who participated in their study.…”
Section: Validation Of Pse Measuresmentioning
confidence: 99%
“…Parenting efficacy was assessed in terms of parents' judgments of their abilities to organize and execute parenting roles and responsibilities to have intended or expected child behavior consequences (Wittkowski et al, 2017). Parenting efficacy beliefs were measured by the Parenting Experiences Scale (Trivette and Dunst, 2004), Personal Assessment of Control Scale (Boyd and Dunst, 1996), Confidence in Parenting Scale (Bailey et al, 2007), and investigator-developed measures.…”
Section: Parenting Efficacy Beliefsmentioning
confidence: 99%